2021
DOI: 10.1002/brb3.2394
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of vitamin B6 as an adjunctive therapy to lithium in improving the symptoms of acute mania in patients with bipolar disorder, type 1; a double‐blind, randomized, placebo‐controlled, clinical trial

Abstract: Objective: Vitamin B6 has been linked to a variety of probable roles, including antiinflammatory, homocysteine-lowering, serotonin-regulating, and dopamine-lowering.In this study, we investigated the possible effect of vitamin B6 on bipolar disorder in manic episode with psychotic feature in a placebo-controlled double-blind clinical trial in a psychiatric hospital. Methods:This study was performed on 50 patients who were equally divided into two groups (each group included 25 patients) using 80 mg of vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…A cross-sectional study revealed that not only the content of vitamin B6 but also the content of minerals such as magnesium and zinc are significantly correlated with mania ( 33 ). Simultaneously, another RCT study on vitamin B6 ( 34 ) showed that after controlling for confounding factors, oral vitamin B6 could not improve the mental health of manic patients. Considering the different conclusions on vitamin B6, we will use the method of Mendelian randomization in the next step to analyse whether there is a causal relationship between vitamin B6 and mania.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study revealed that not only the content of vitamin B6 but also the content of minerals such as magnesium and zinc are significantly correlated with mania ( 33 ). Simultaneously, another RCT study on vitamin B6 ( 34 ) showed that after controlling for confounding factors, oral vitamin B6 could not improve the mental health of manic patients. Considering the different conclusions on vitamin B6, we will use the method of Mendelian randomization in the next step to analyse whether there is a causal relationship between vitamin B6 and mania.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to a possible increase in lithium plasma concentrations when taking cyclooxygenase inhibitors, these should be closely monitored when taken currently. Neither adjuvant levetiracetam nor adjuvant vitamin B 6 to lithium significantly improved mania symptoms or sleep quality (Badrfam et al 2021;Keshavarzi et al 2022). Additional medication with agomelatine did not achieve a significant improvement in MADRS scores in depressed patients (Yatham et al 2016b).…”
Section: Additional Medication Without Effectmentioning
confidence: 99%
“…Three studies on vitamin supplementation were conducted in the period examined [114,123,131]. As vitamin D supplementation seems to improve symptoms of unipolar depression, Marsh et al [114] administered 5000 IU/day of vitamin D for 12 weeks to patients suffering from BD and hypovitaminosis D, but did not find improvements in depressive, anxious, and manic symptoms measured with the Montgomery-Åsberg Depression Rating Scale (MADRS), the Hamilton Anxiety Rating Scale (HAM-A), and the Young Mania Rating Scale (YMRS).…”
Section: Bipolar Disordermentioning
confidence: 99%
“…Furthermore, as vitamin B6, in addition to having an anti-inflammatory effect and reducing homocysteine, plays a role in serotonin and dopamine regulation, two studies were conducted on this agent. In the first study, [123] vitamin B6 (80 mg) was administered daily in BD patients during a manic episode with psychotic manifestations in association with lithium. No significant differences in mood were observed in patients compared to controls.…”
Section: Bipolar Disordermentioning
confidence: 99%